The Relationship Between Bankruptcy Risk and Growth for Non-Listed Firms - Kjell Bjørn Nordal; Randi Næs (Norges Bank, 2010)
We investigate the relationship between bankruptcy risk and expected future sales growth for Norwegian non-listed firms for the period 1988-2007. We find that firms with high bankruptcy risk also have high expected future growth. Financial ratios characterizing firms with high bankruptcy risk also characterize firms with high future expected growth. Small firms, firms with low levels of equity and retained earnings, firms with low profitability and low levels of sales per unit of capital, have all higher expected future growth rates than other firms. These findings suggest a tradeoff between the upside potential of high growth and the downside risk of bankruptcy.
hdl:11250/2497429
Keywords: G10; G30; G33; 330; non-listed firms; growth; bankruptcy risk